2020
DOI: 10.1248/bpb.b19-00786
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Inflammatory Bowel Disease in Mice by Regulating SUMO1

Abstract: Resveratrol (Res) is a natural active antioxidant that is effective in relieving inflammatory bowel disease (IBD). However, the specific mechanism for its function is unknown. In our study, dextran sodium sulfate (DSS)-induced mouse IBD disease model was constructed. All mice were randomly divided into three groups. The treatment effects of resveratrol on IBD were evaluated by observing the body weight, fecal traits, colon/ spleen gross appearance, tissue hematoxylin-eosin (H&E)/immunohistochemistry (IHC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Furthermore, we can demonstrate significant alleviation of intestinal inflammation and inhibition of tumor growth with several aspirin-resveratrol derivatives (Figures 5 and 6A). Previous reports have confirmed our observations including a recent publication by Sudha et al (2020) [52] to demonstrate tumor reduction by resveratrol and publications by Wang et al (2019) [53] and Zhang et al (2019) [54] that demonstrated the beneficial effect of resveratrol on DSS-induced colitis but at 80,100 mg/kg resveratrol use. In addition, cell-based modulation of follicular tumorigenesis (at 300 µM) [55] highlights the importance of our findings at 50-100 µM for our resveratrol derivatives.…”
Section: Salicylate Derivatives Of Resveratrol Have More Defined Targetssupporting
confidence: 91%
“…Furthermore, we can demonstrate significant alleviation of intestinal inflammation and inhibition of tumor growth with several aspirin-resveratrol derivatives (Figures 5 and 6A). Previous reports have confirmed our observations including a recent publication by Sudha et al (2020) [52] to demonstrate tumor reduction by resveratrol and publications by Wang et al (2019) [53] and Zhang et al (2019) [54] that demonstrated the beneficial effect of resveratrol on DSS-induced colitis but at 80,100 mg/kg resveratrol use. In addition, cell-based modulation of follicular tumorigenesis (at 300 µM) [55] highlights the importance of our findings at 50-100 µM for our resveratrol derivatives.…”
Section: Salicylate Derivatives Of Resveratrol Have More Defined Targetssupporting
confidence: 91%
“…showed that RSV treatment significantly inhibited the severity of UC and dramatically reduced the expressions of TNF-α, IL-8, IFN-γ, p22, and gp91 relative to the UC control group, highlighting the antioxidant effects of RSV on preventing oxidative damage induced by DSS ( Yao et al, 2010 ). IL-10 serves as an anti-inflammatory cytokine, which is increased after RSV administration in inflammatory bowel disease ( Wang J. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was reported that down-regulation of Sirt1 at least partially suppressed the effects of resveratrol-promoting chemopreventive and anti-tumorigenic effects in CRC cells [ 36 ]. In addition, resveratrol has also been shown to downregulate inflammation in colorectal cancer by suppressing the expression of SUMO1 (small ubiquitin-like modifier protein 1) and nuclear translocation, thereby suppressing the Wnt/β catenin pathway [ 77 ].…”
Section: Discussionmentioning
confidence: 99%